Perbandingan Pertumbuhan dan Produksi Ubikayu (Manihot esculenta Crantz) di Lahan Tanjung Bintang Akibat Pemberian Pupuk Mikro - Tamara, Tyas; Utomo, Setyo; Setiawan, Kukuh; Yuliadi, Erwin (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
This research aims to evaluate the effect of addition of micro fertilizer on the cassava production in cassava plants (Manihot esculenta Crantz). This research was carried out in the dry land of Sukanegara Village, Tanjung Bintang, South Lampung from July 2018 to May 2019. The clones used were CMM 252757 080915-15, Cimanggu 12 080915, Mulyo 240715-10, Malang 6 240815-3, BW 1, BL 8 150815-3, Darul Hidayah 240815-4 and UJ 5 (as comparable clone) with a spacing of 1m x 0.5m. The treatment was arranged in factorial (8x2) in a randomized block design with three replications. The first factor was eight cassava clones CMM 252757 080915-15, Cimanggu 12 080915, Mulyo 240715-10, Malang 6 240815-3, BW 1, BL 8 150815-3, Darul Hidayah 240815-4 and UJ 5 (as comparison clones). The second factor was two levels of Zinc Micro fertilizer dosage, which were 0 kg ha-1 and 20 kg ha-1. The variables observed were plant height, number of leaves, number of root per plant and weight root per plant. Data were analyzed using the SAS 9.0 application at significant level 5%. The results showed that the variable plant height, number of leaves at the age of 4 to 8 Month After Planting (MAP), the number of root and the weight of root per plant had a significant effect due to clones. Whereas, the addition of micro fertilizer 20 kg ha-1 had a significant effected on plant height at the age of 4 and 10 MAP then the addition of micro fertilizer also significantly affected the number of root per plant, but did not affect the weight of root per plant. The results showed that the addition of 20 kg Zinc Micro ha-1 was able to produce 9 root per plant in BW 1 and Malang 6 clones. Meanwhile, the weight of Malang 6 clone showed the highest root weight as 6.133 g per 5 plants. In addition, the highest range of starch content is produced by Darul Hidayah clone, as 28% due to the addition of 20 kg of Zinc Micro ha-1.